Fossils remains of even-toed ungulates from the Middle Siwaliks, Punjab, Pakistan. (2nd September 2021) - Draz, Omer; Samiullah, Khizar; Asrar, Muhammad; Rasul, Azhar; Yasin, Riffat; Khan, Luqman
ABSTRACT: The Dhok Pathan Formation of Middle Siwaliks is remarkably rich for the fossils of ungulates. The fauna consists of Cervidae, Giraffidae, Tragulidae and Suidae but the fossils of family bovidae are more abundant. The 23 collected and described specimens here belong to seven species which are Selenoportax vexillarius, Pachyportax latidens, Miotragocerus cf. gluten, Gazella lydekkeri, Dorcatherium majus, Propotamochoerus hysudricus and Tetraconodon cf. magnus . The described material consists of both upper and lower dentition. The fossil-bearing locality is located near Padhri village 55 km away from the tehsil Dina, district Jhelum. It is mainly composed of claystone, sand-stone and siltstone beds. The studied locality dated to Late Miocene. This Formation was deposited in subtropical condition. Bovids were predominant in Padhri, which indicate the highly moist conditions with small but numerous open standing water bodies.